Analisa Cacat Las GMAW Pada Proses Pabrikasi Bak Dump Truck Menurut AWS D1.1 2015 Dengan Metode Inspeksi Visual di PT Metalindo Teknik Utama - Pratama, Dani Nugraha; Rizal Hanifi; Ratna Dewi Anjani (Jurnal Serambi Engineering, 2026)
The welding quality of dump truck fabrication plays a crucial role in ensuring structural strength and production reliability. The Gas Metal Arc Welding (GMAW) process has the potential to generate welding defects when welding parameters and material preparation are not properly controlled. This study aims to identify welding defects occurring in the fabrication process at PT Metalindo Teknik Utama and to evaluate their acceptance based on the AWS D1.1:2015 criteria through visual inspection. Visual inspection was conducted on several weld joints using a welding gauge and vernier caliper to measure undercut depth, reinforcement height, and surface defects. The results show six types of welding defects, namely undercut, spatter, porosity, pin hole, surface cold lap, and excessive capping. According to AWS D1.1:2015, three defects were classified as rejected (undercut of 1.25 mm, pin hole >3 mm, and 4 mm capping), while spatter, porosity, and surface cold lap were considered accepted. These defects were mainly caused by improper welding parameters, insufficient welding technique control, and inadequate surface preparation. Corrective actions such as grinding, gouging, and re-welding were applied. The results indicate that visual inspection based on AWS D1.1:2015 is effective in evaluating weld quality and supporting improvement in the production process.